"A narrow bridge home": The dorsal mesentery in primordial germ cell migration. (August 2019) - Hen, Gideon; Sela-Donenfeld, Dalit
Highlights: Early migration routes of PGCs differ among vertebrates. Yet, at the end of their journey they all reach the dorsal mesentery and migrate to the gonads. The dorsal mesentery in the hind-gut level displays left-right asymmetry in tissue architecture, cell density as well as molecular properties. The left-right asymmetry along the dorsal mesentery may play a role in guiding PGCs to the genital ridges. Various ECM and adhesion molecules are expressed in the dorsal mesentery. Further research is needed to reveal their role in PGC migration in vivo. The signaling systems SDF1/CXCR4 and CSF/c-kit are essential for PGC migration in the dorsal mesentery. Abstract: Specification of primordial germ cells (PGCs) in all vertebrates takes place in extragonadal sites. This requires migration of PGCs through embryonic tissues towards the genital ridges by both passive and active types of migration. Commonly, colonization in the genital ridges follows migration of the PGCs along the thin tissue of the dorsal mesentery. Here we review the anatomy of the dorsal mesentery, the role it plays in migration of PGCs, and the interactions of PGCs with different cell types, extracellular matrix and signaling pathways that are all essential for attraction and orientation of PGCs along the dorsal mesentery towards the gonad anlage.